Asean Law And Economic Growth Asean - Nairobi Nairobi; Debby Anggun Kenita (Ecoplan, 2021)
The ASEAN Economic Community, commonly referred to as AEC (ASEAN Economic Community) in 2015, is a form of cooperation between ASEAN member countries by integrating the economic sector in a single market in the Southeast Asia region. This is also an answer to investors' questions regarding the accessibility of investment destination countries, including legal certainty. This study aims to analyze the effect of law enforcement on economic growth. The role of the government in law enforcement is expected to be able to support the economic development of a country. The data used in this study include economic growth, the rule of law, voice and accountability, foreign direct investment, employment, and the initial development of 10 ASEAN member countries for the 2007-2018 period. The method used is panel data regression and testing the significance of the model. The method used is the Random Effect Model. The results show that the rule of law, foreign direct investment, labor, and initial growth have a significant and positive effect on economic growth in ASEAN. In contrast, voice and accountability significantly impact ASEAN economic growth in the 2007-2018 period.